Introducing urban conviviality to enhance tourist satisfaction a case study of the third places in Davao City - Mernilo, Ernest James S. (2023)
This study examines the significance of Urban Tourist Spots (UTS) in shaping city life and accommodating various activities, with a focus on third places that foster community and social relationships. The research aims to evaluate existing third places in Davao City, assess tourist satisfaction, and identify areas for improvement to enhance urban conviviality. The study used a mixed-methods approach, including online surveys, qualitative observations, and photographic documentation. Findings showed that certain qualities such as safety, surrounding buildings, aesthetics, and seating scored well across all UTSs, but aspects like control, scale, edge effect, livability, and vitality scored lower, indicating areas for improvement. The study also explored the connection between respondents' demographics and their satisfaction with urban convivial spaces, highlighting the need for tailored designs for different user groups. The research provides insights for architects and urban planners to create UTSs that promote conviviality, inclusivity, and social cohesion. The findings contribute to the formulation of design guidelines to create more convivial third places, emphasizing the importance of understanding users and planning for all age groups. This inclusive approach can be implemented on a large scale through the development of urban spaces with walkable pathways and functional arrangements, as well as through architectural details that cater to the needs of all user groups, including special provisions for the physically challenged and visual ornamentation.